Comparison on the application of the software for image-free control UAV data processing of digital landslide: A case study of Huangtupo landslide in the Three Gorges Reservoir area - Yujian HE; Jie DOU; Xiekang WANG; Yonghu FU; Hao MA; Heng WANG (Zhongguo dizhi zaihai yu fangzhi xuebao)
Landslide disasters are among the most prevalent geological hazards in China, which seriously threatens the safety of people's lives and property. Efficient, convenient, and accurate digital landslide analysis is crucial for landslide disaster prevention and mitigation. In recent years, image-free unmanned aerial vehicle (UAV) aerial survey technology has been increasingly employed in digital landslide analysis due to its advantages of high processing efficiency and production of high-quality maps. This study aims to explore the advantages and disadvantages of various aerial survey software based on image-free control technology in landslide terrain processing, as well as their feasibility in digital landslide applications. In this paper, the Huangtupo landslide in the Three Gorges reservoir area of the Yangtze River is selected as the research object. High-resolution remote sensing data in the study area are obtained using the Dajiang PHANTOM 4RTK UAV. Four commonly used professional aerial survey processing software, namely Pix4D Mapper, Photoscan, Context Capture, and DJI Terra, are utilized for digital processing. A comparative analysis is conducted based on four aspects: orthophoto quality, accuracy error, time consumption, and operation difficulty. The research findings reveal that: (1) Under the condition of a single landslide aerial photography area of up to 2.23 km2, Pix4D Mapper software generates orthophoto maps of the highest quality that meet the requirements for large-scale mapping; (2) DJI Terra and Pix4D Mapper have the best performance in terms of accuracy error, with the mean square error of 20 inspection points in the plane and vertical axis not exceeding 10cm and 30cm, respectively. Comprehensive comparison results indicate that Pix4D Mapper software demonstrates the most advantages in analyzing large-scale individual landslide disasters; (3) Based on the remote sensing interpretation of digital landslide maps, the basic digital information of the landslide is obtained, and a comprehensive landslide disaster database is established by storing the digital landslide information using GIS software. In conclusion, image-free UAV aerial survey technology holds significant advantages in the rapid establishment of future landslide disaster databases, emerging as an important research direction that provides technical and data support for swift analysis of landslide disaster prevention and emergency investigations.